Biochar and the district heating system: An investigation of how a district heating system may benefit from the implementation of a biochar production plant - Nilsson, Fanny; Rosén, Sofia (My University, 2021)
In 2017, Sweden established a long-term climate goal of being CO2 -neutral by 2045 [1]. In order to reach this goal, 15% reduction of the CO2 can be constituted of complementing measures, such as bioenergy carbon capture and storage (BECCS) and biochar. In line with the climate goal of Sweden, Göteborg Energi has set a goal of having a 100% renew able and recycled district heating system (DHS) by 2025. Biochar is one of the possible technologies that could contribute in reaching this goal. The DHS in Gothenburg was modelled through a Linear Programming (LP) model in the software General Algebraic Modeling System (GAMS). A yearly biochar demand of 35,750 MWh, approximately 5500 tonne, was implemented. The model invested in the most suitable capacity for the biochar plant to fulfill the demand while keeping the yearly cost of the system as low as possible. Apart from producing biochar, the plant produce excess heat. In the model, the plant could choose to sacrifice biochar to only produce heat, providing some extra flexibility to the DHS. To investigate the robustness of the results the following parameters were evaluated in different scenarios: biochar demand, discount rate, variable cost, feedstock price, biochar price and reduction in investment cost. The primary results showed no utilisation of flexibility and the capacity of the plant was instead decided by the biochar demand. The excess heat acted as a base load in the DHS during winter and the load of the plant was used to cover fluctuations in heat demand during summer. Flexibility was, however, initiated in four out of six scenarios. At low feedstock prices around 50-110 SEK/MWh, the production of extra heat amounted to approximately 9400 and 1000 MWh respectively. Further, a price of biochar have a significant impact on the investment of the biochar plant as increased prices shift the driving parameter from demand to generating an income to the DHS. With suitable economic parameters, a biochar plant could offer both carbon negative DH as well as an energy buffer to the DHS. As flexibility is initiated between biochar and heat, the biochar plant becomes more of a intermediate load than a base load. There is still a scarcity in research regarding the technical possibilities of shifting from biochar to heat production, thus, more research is needed within this area.
Keywords: biochar; carbon sequestration; district heating; energy system modelling; linear programming; pyrolysis; biomass